MAKNA LABA BAGI PETANI KOPI (STUDI KASUS DI DESA SUMBERMANJING WETAN, KECAMATAN SUMBERMANJING WETAN, KABUPATEN MALANG) - Alces Putra Alkaf; Moh. Amin; Siti Aminah Anwar (Universitas Islam Malang, 2022)
This study aims to determine the meaning of profit for coffee farmers in Sumbermanjing Wetan Village. The research location is in the coffee cultivation area of Sumbermanjing Wetan Village, Sumbermanjing Wetan District, Malang Regency. This research is a qualitative descriptive study. Data collection techniques using interviews, observation and documentation studies. The data analysis technique of this research uses an analytical approach, namely qualitative descriptive analysis. Based on the results of data analysis, the meaning of profit for coffee farmers is a life-sustaining component, namely to meet individual and family needs such as food, clothing, housing, and to meet children's educational needs. There are 2 types of operational financing which are divided based on private ownership of land and land cultivated by farm laborers. The welfare felt by coffee farmers in Sumbermanjing Wetan Village is considered insufficient because the income earned has not been able to meet the overall needs of farmers and their families. Social status among petuni is considered equal, but not for civil servants and farmers. There is discrimination based on differences in the income of farmers who are considered to be lower than civil servants.Keywords: Meaning of Profit, Income, Cost, Welfare, Social Status